The Role of Religious Organizations in Child Marriage Prevention and Handling during Pandemic - Rofiah, Siti; Fauzi, Moh.; Muqoddam, Fakih (Universitas Islam Sultan Agung, 2022)
In Indonesia, religious leaders are in a strategic position. Their existence can affect people's lives in various aspects, not least in the context of marriage. During the COVID-19 pandemic, the number of child marriages in Central Java rose sharply. Based on the background above, the questions are how religious leaders view this problem and what the roles to be performed in the context of prevention and treatment. This type of research is field research with a qualitative approach. The data collection technique is done by interview and documentation. The informants are administrators of two major religious organizations in Indonesia, namely NU and Muhammadiyah. The results showed that; First, the existence of religious organizations did not have a significant role in preventing and handling child marriage cases in Central Java. Secondly, the existence of religious organizations has no relevance to the high and low rate of child marriage in Central Java. Third, the existence of religious leaders is still seen as having authority in the community to support the success of the prevention and handling of child marriage programs